1987
DOI: 10.1002/dev.420200107
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral states of premature infants: Implications for neural and behavioral development

Abstract: Nine premature and 28 full-term infants were observed in their homes for 7 hr when they were 2, 3, 4, and 5 weeks post-term, and the sleeping and waking states displayed by these infants were compared. For these comparisons, the observation day was divided into two mutually exclusive contexts: times when the baby was alone and times when the baby was with the mother. The premature infants spent more time alone (mean of 5.4 hr a day) than the full-terms (4.6 hr). Over the total 7-hr day, the premature infants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Anders and Keener (1985) and Davis and Thoman (1987) report results that support the notion that preterm infants have a lower level of behavioral arousal whether asleep or awake which results in less time in interaction with their parents. In addition, Telzrow, Kang, Mitchell, Ashworth, and Barnard (1980) found that preterm infants tended to show an all-or-none response to stimulation and were more difficult to maintain in a quiet-awake state.…”
Section: Infant Characteristicssupporting
confidence: 72%
“…Anders and Keener (1985) and Davis and Thoman (1987) report results that support the notion that preterm infants have a lower level of behavioral arousal whether asleep or awake which results in less time in interaction with their parents. In addition, Telzrow, Kang, Mitchell, Ashworth, and Barnard (1980) found that preterm infants tended to show an all-or-none response to stimulation and were more difficult to maintain in a quiet-awake state.…”
Section: Infant Characteristicssupporting
confidence: 72%
“…Sleep measures have been demonstrated to be very sensitive indices of central nervous system functional status. 9,11,[25][26][27][28] Our MMS assessment was not performed during the earlier course of the intervention; therefore, we do not have data regarding the acute effects of NIDCAP on sleep. The hypothesis that there is improved central nervous system development as measured by sleep quantity and maturation resulting from individualized developmental (NIDCAP) care was not supported by the sleep measures in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These altered conditions promote longer bouts of wakefulness and a greater percentage of wakeful state over a 24-hour period [38][39][40] . Such an adaptive response consequentially places the child at increased risk for disease through depletion of energy reserves and excessive stimulation of receptive neuronal networks.…”
Section: Sleep Ontogenesis -Continuities and Discontinuities Of Statementioning
confidence: 99%